2003
DOI: 10.1097/00006199-200305000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Sleep Quality and Fatigue Correlates With Actigraphy in Midlife Women With Fibromyalgia

Abstract: Self-reported sleep quality and fatigue are associated with behavioral indicators of sleep quality at home in women with FM. Actigraphy is a useful objective measure of improved sleep outcomes in intervention studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 27 publications
2
48
0
Order By: Relevance
“…Actigraphy is becoming a popular method of assessing total sleep time and movement during sleep, a measure of WASO. 8,13,14 We also included a subjective sleep assessment in our study, as this form of assessment provides valuable information regarding an individual's perception of their sleep. 15,16 Furthermore, subjective sleep estimates tend to differ from objective measurements of sleep, 15,17,18 and therefore it is important for studies to include both assessments when investigating sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Actigraphy is becoming a popular method of assessing total sleep time and movement during sleep, a measure of WASO. 8,13,14 We also included a subjective sleep assessment in our study, as this form of assessment provides valuable information regarding an individual's perception of their sleep. 15,16 Furthermore, subjective sleep estimates tend to differ from objective measurements of sleep, 15,17,18 and therefore it is important for studies to include both assessments when investigating sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring in the Sleep Disorder Unit was started. [6,20]. In most studies, sleep disorders have been found at a high rate in these patients [4,5].…”
Section: Casementioning
confidence: 99%
“…Only two studies, used polysomnography, a gold-standard measurement [16,17], where research revealed a longer time to fall asleep (sleep latency), frequent episodes of awakenings, restlessness, and a shorter sleep duration. In recent years, researchers have chosen to use the actigraph as an auxiliary tool to study sleep habits in special populations, such as rheumatoid arthritis (RA) [18], primary Sjögren's syndrome (pSS) [19] osteoarthritis [20], fibromyalgia [21,22], chronic back pain [23], breast cancer [24], and recently SLE [25].…”
Section: Introductionmentioning
confidence: 99%